ENVIRONMENTAL PROTECTION IN THE PERSPECTIVE OF THE PRINCIPLE OF STATE RESPONSIBILITY - nilam hidayah nilam hidayah; Pamungkas Satya Putra (Law Faculty of Universitas Bandar Lampung, 2022)
Setiap orang berhak hidup dalam lingkungan hidup yang baik dan sehat, hal ini tertuang dalam UUD Pasal 28H Ayat ( 1 ). As a country that is carrying out a sustainable development process, Indonesia emphasizes that the earth, water and the wealth in it are controlled by the state to support welfare. public. Exploitation of natural resources continues, one of which is taking coal in South Kalimantan. A decree regarding coal production in the area has been issued, but negative reactions have been given by the community around the mining area and the Indonesian Forum for the Environment. This research describes mining by raising the study of coal mining permits in South Kalimantan. The research method uses qualitative methods, namely procedures that present descriptive data from social observations in people's lives. Referring to the title, this research uses a case study. Research conducted in an incentive at an institution and certain symptoms (Arikunto, 2002: 14). The purpose of this research is to study and analyze the application of the principle of state responsibility from the cancellation of the Decree of the Minister of Energy and Mineral Resources of the Republic regarding mining permits in the South Kalimantan region. Keyword: Environment, Coal, State Responsibilities.